Severe Erythema Nodosum Leprosum Complicated by Warm Autoimmune Hemolytic Anemia: Navigating the Immunosuppressive Paradox - Devina Ravelia Tiffany Subroto; Kadek Cahya Adwitya; I Putu Bayu Triguna (HM Publisher, 2026)
Erythema nodosum leprosum (ENL) is a severe, systemic immune-complex mediated complication of multibacillary Hansen’s disease. While anemia of chronic disease is frequently observed in leprosy, the concurrent development of Warm Autoimmune Hemolytic Anemia (wAIHA) is an exceptionally rare and precarious clinical entity. This comorbidity creates a therapeutic paradox wherein the high-dose corticosteroids required to halt hemolysis may exacerbate the risk of sepsis in patients with necrotic skin lesions and compromised barrier function. We report the case of a 42-year-old male with multibacillary Hansen’s disease on multidrug therapy who presented with high-grade fever, progressive fatigue, and necrotic cutaneous lesions. Laboratory evaluation revealed life-threatening normocytic normochromic anemia (Hemoglobin 3.5 g/dL) and a leukemoid reaction (WBC 42,540/µL). Hemolysis was confirmed by elevated lactate dehydrogenase (564 U/L), indirect hyperbilirubinemia, and a strongly positive direct Coombs test (IgG). A diagnosis of wAIHA secondary to severe necrotic ENL was established. Standard high-dose pulse steroid therapy was deemed high-risk due to the patient’s extreme neutrophilia (NLR 80.25) and open necrotic ulcers. Consequently, a tailored regimen of intermediate-dose intravenous methylprednisolone (62.5 mg twice daily) combined with broad-spectrum antibiotics was initiated. This strategy successfully suppressed hemolysis and resolved the ENL reaction without precipitating secondary opportunistic infections. In conclusion, the coexistence of wAIHA and ENL suggests a shared mechanism of dysregulated T-cell immunity and molecular mimicry. This case demonstrates that in scenarios involving high infectious risk, an individualized, intermediate-dose corticosteroid protocol can achieve remission while mitigating the dangers of profound immunosuppression.